Selective Sparing of Striatal Interneurons after Poly (ADP-Ribose) Polymerase 1 Inhibition in the R6/2 Mouse Model of Huntington’s Disease - Paldino, Emanuela; Cardinale, Antonella; D’Angelo, Vincenza; Sauve, Ilaria; Giampà, Carmela; Fusco, Francesca R. (Frontiers in Neuroanatomy, 2017)
Poly (ADP-ribose) polymerases (PARPs) are enzymes that catalyze ADP-ribose units transfer from NAD to their substrate proteins. It has been observed that PARP-1 is able to increase both post-ischemic and excitotoxic neuronal death. In fact, we have previously shown that, INO-1001, a PARP-1 inhibitor, displays a neuroprotective effect in the R6/2 model of HD. In this study, we investigated the effects of PARP-1-inhibition on modulation of pCREB (phosphorylated c- AMP response element binding protein) and CBP (CREB-binding protein) localization in the different striatal neuronal subsets, and on the neurodegeneration of selected interneurons that are a particularly vulnerable subclass of striatal neurons. Transgenic mice were treated with INO-1001 (10 mg/Kg daily) starting from 4 weeks of age. Double-label immunofluorescence was performed to value the distribution of CBP in ubiquitinated NIIs (Neuronal intranuclear inclusions) in the striatum. INO-1001-treated and saline-treated brain sections were incubated with: goat anti-choline acetyl transferase; goat anti-nitric oxide synthase; mouse anti-parvalbumin and mouse anti-calretinin. Morphometric evaluation and cell counts were performed. Our study showed that the PARP inhibitor has a positive effect in sparing parvalbumin and calretinin-containing interneurons of the striatum, where CREB was upregulated. Moreover, INO-1001 promoted CBP localization into the nuclei of the R6/2 mouse. The sum of our data corroborates the previous observations indicating PARP inhibition as a possible therapeutic tool to fight Huntington’s disease.